Oddziaływanie kryzysu gospodarczego na politykę podatkową na przykładzie działalności rolniczej - Konopska-Struś, Emilia; Struś, Mirosław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Economic crises as an integral part of the business cycle periodically occur in the economy, leading to its collapse. State economy is exposed during the crisis period to the numerous negative phenomena such as the increase in unemployment, financial problems, a sense of uncertainty. During the economic crisis increases the risk of lower budget revenues, which is not conducive to reform the tax system, even if they could lead to long-term benefits for the economy. These problems are well illustrated by the situation in agriculture. For many years there are discussed about the income taxation of agricultural activity. In June of 2013 it was prepared a project of income taxation of agricultural activity, but it was abandoned in the end. The article attempts to answer the question: is there a connection between the economic crisis and the failure to tax reform agriculture? There were subjected to a critical analysis of project assumptions of income taxation of agricultural activities and estimated potential revenues of the budget of municipalities in this respect. The available estimates indicate that the failure of the tax reform in agriculture could affect the precarious financial situation of the state budget and municipal budgets due to the economic crisis.
Keywords: agricultural tax; agricultural activity; income tax; economic crisis